Aplikasi Searching Nama Sekolah Berbasis Android (Studi Kasus : Dinas Pendidikan Labuhanbatu Selatan) - Widodo, Dodi Surya (Universitas Labuhanbatu, 2021)
The development of information technology is currently experiencing very rapid progress, especially computers that have a very important role in every human activity, so that humans in doing their jobs always need computers. Along with the times, technology will also progress. And the more developed an area, the more educational institutions will be established, therefore it is necessary for a school search application to make it easier for smartphone users to search schools in the area. The purpose of this school search application is to make it easier for application users to search for existing school data. This school search application is based on Android with the Eclipse and SQlite programming languages.